Deep Learning Strategies as a Moderator of the Influence of Spiritual Habituation and Teacher Support on Students Islamic Character - Nelly Gusri; Abdul Madjid (Journal in Teaching and Education Area, 2026)
The formation of Islamic character is a primary objective of Moral Faith learning in secondary schools, yet its achievement is influenced by pedagogical and spiritual factors. This study aims to examine the effects of teacher support and spiritual habituation on students’ Islamic character, as well as the mediating role of deep learning. A quantitative approach was employed involving 48 students of SMA Muhammadiyah 5 Yogyakarta selected through saturation sampling. Data were collected using a Likert-scale questionnaire and analyzed using SEM-PLS with SmartPLS 3. The results indicate that teacher support has a positive and significant effect on deep learning and Islamic character, while spiritual habituation significantly influences deep learning but not Islamic character directly. Deep learning does not significantly affect Islamic character and does not mediate the proposed relationships. These findings highlight the central role of teachers and contextual spiritual reinforcement in shaping students’ Islamic character.